On the effect of taxation in the online sports betting market - Juan Vidal-Puga (SERIEs - Journal of the Spanish Economic Association, 2017)
We analyze the effect of taxation in the online sport betting market. A relevant characteristic of this market is its negligible marginal cost on bet volume. Taxation can be on gross profit (Gross Profit Tax) or on volume (General Betting Duty). We model the two most popular online sport betting bets: fixed-odds and spread, as compared with another traditional sport betting: parimutuel. We characterize the odds and the bookmaker's payoff in (strong) subgame perfect equilibrium for each of the three types of bets under both taxation schemes. The results show that taxation on gross profit maximizes the utilitarian social welfare. Moreover, the three types of bets are equivalent when the market is symmetric.
Keywords: C72; D42; L83; 330; Taxation; Online betting market; Sport betting; Bookmaker